Strategi Komunikasi Pemasaran Pit-Stop Kopi KIG Gresik dalam Mempertahankan Loyalitas Pelanggan - Rama Purba Dewa; Didik Tranggono (Universitas Merdeka Malang, 2022)
Pit-Stop Kopi KIG is one of the cafes with the nuances of a warung in Gresik Industrial City which was established in2019. This consumer cafe continues to increase every year. With various marketing communication strategies used. This study aims to determine the marketing communication strategy of Pit-Stop Kopi (KIG) Gresik in maintaining customer loyalty. This study uses a descriptive approach by collecting factual data based on the results of observations, study documentation, interviews with area supervisors, and the creative director of Pit-Stop KIG accompanied by five loyal customers, five new customers and one expert informant to complete the research data. The selected subjects used in-depth interview techniques. The results showed that Pit-Stop Kopi did a marketing communication strategy to maintain customer loyalty. The marketing communication strategy taken is advertising, promotion, service, product, place, physical evidence and process. This KIG Pit-stop also determines the communication channel for ordering by using interpersonal, impersonal channels, and determines the consumer aspect.Keywords: Strategy, Marketing Communication, Consumer Loyalty, Coffee Shop